2014
DOI: 10.1007/s11695-014-1340-9
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Laparoscopic Sleeve Gastrectomy in Treating Adolescent Obesity

Abstract: SG seems to be an effective and safe bariatric procedure in obese adolescents, as it can significantly decrease excess body weight and reduce co-morbidities in a relatively short period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 12 publications
2
15
0
3
Order By: Relevance
“…These findings may explain our borderline association of the rs9939609 with the BMI; however, this needs to be replicated further in other cohorts in the population. The FTO variant has been reported to be involved in weight regain after bariatric surgery [23] which is considered a common obesity intervention in the Kuwaiti population [24], and therefore identifying patients at high risk of weight regain prior to intervention may help in planning the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may explain our borderline association of the rs9939609 with the BMI; however, this needs to be replicated further in other cohorts in the population. The FTO variant has been reported to be involved in weight regain after bariatric surgery [23] which is considered a common obesity intervention in the Kuwaiti population [24], and therefore identifying patients at high risk of weight regain prior to intervention may help in planning the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In morbidly obese adolescent with coexisting comorbidities and no response to non-surgical therapy, surgery should be offered early in life before these conditions become irreversible. [14][15][16] In present study, overall post-operative complication rate was 5.0 % (two cases). These included one cases of gastroesophageal reflux disorder, and two cases of protein caloric malnutrition were identified.…”
Section: Discussionmentioning
confidence: 78%
“…Bariatric surgery is, in fact, highly effective within the adolescent population and can result in loss of 58–73% of excess weight(18, 3340) (Figure 1). Although fewer studies have been performed in this population and long-term follow-up data are only now evolving, the initial studies(1518, 41) show that T2D remission mirrors that which is observed in older patients. In a large, recent 3-year longitudinal study of adolescent bariatric surgery(16) (Table 1), 95% of patients with T2D at baseline exhibited remission by 3 years; prevalence of remission did not differ after VSG versus RYGB, but this may reflect the relatively small numbers of patients with T2D in the study (13%).…”
Section: Bariatric Surgery As a T2d Treatmentmentioning
confidence: 98%
“…Inspired by success as a treatment for adult obesity, bariatric surgery has recently emerged as a treatment for adolescent patients as well. Clinical studies (1014) demonstrate a clear effect of bariatric surgery to improve glycemic control and often elicit complete remission of T2D, including in adolescents (1518). This review will discuss the potential for bariatric surgery as a treatment for T2D in obese and overweight adolescents.…”
Section: Introductionmentioning
confidence: 99%